An Introduction to Nutrition (Open textbook library., 2012)
Welcome to Essentials of Nutrition: A Functional Approach! This book is written for students who are not majoring in nutrition, but want to learn about the fundamental aspects of nutrition and how it applies to their own lives. We have written this book with the assumption that you have little or no prior knowledge of college level chemistry, biology, or physiology. But that does not mean it’s not scientific! Nutrition is a science-based discipline, so all the material included is backed up by rigorous scientific research, but it is presented in a clear, easy-to-understand fashion without requiring a background in science.